Elevated inorganic carbon and salinity enhances photosynthesis and ATP synthesis in picoalga Picocystis salinarum as revealed by label free quantitative proteomics - Singh, Jyoti; Kaushik, Shubham; Maharana, Chinmaya; Jhingan, Gagan Deep; Dhar, Dolly Wattal (Frontiers in Microbiology, 2023)
Saline soda lakes are of immense ecological value as they niche some of the most exclusive haloalkaliphilic communities dominated by bacterial and archaeal domains, with few eukaryotic algal representatives. A handful reports describe Picocystis as a key primary producer with great production rates in extremely saline alkaline habitats. An extremely haloalkaliphilic picoalgal strain, Picocystis salinarum SLJS6 isolated from hypersaline soda lake Sambhar, Rajasthan, India, grew robustly in an enriched soda lake medium containing mainly Na2CO3, 50 g/L; NaHCO3, 50g/L, NaCl, 50 g/L (salinity ≈150 ‰) at pH 10. To elucidate the molecular basis of such tolerance to high inorganic carbon and NaCl concentrations, a high-throughput LFQ (label-free quantitation) based quantitative proteomics approach was applied. Out of the total 383 proteins identified in treated samples, 225 were Differentially abundant proteins (DAPs), of which 150 were statistically significant (p value <0.05) including 70 upregulated and 64 downregulated proteins after 3 days of growth in highly saline-alkaline medium. Most DAPs are involved in photosynthesis, oxidative phosphorylation, glucose metabolism and ribosomal structural components envisaging that photosynthesis and ATP synthesis were central to the alkalinity-salinity response. Key components of photosynthetic machinery like photosystem reaction centres, ATP synthase, Rubisco, Fructose-1,6-bisphosphatase, Fructose-bisphosphate aldolase were highly upregulated. Enzymes Peptidylprolyl isomerases (PPIase), important for correct protein folding showed remarkable marked-up regulation along with other chaperon proteins indicating their role in osmotic adaptation. Enhanced photosynthetic activity exhibited by Picocystis salinarum in highly saline-alkaline condition is noteworthy as photosynthesis is suppressed under hyperosmotic conditions in most photosynthetic organisms. The study provided the first insights into the proteome of extremophilic alga P. salinarum exhibiting extraordinary osmotic adaptation and proliferation in polyextreme conditions prevailing in saline sodic ecosystems, potentially unraveling the basis of resilience in this not so known organism and paves the way for a promising future candidate for biotechnological applications and model or¬ganism for deciphering the molecular mechanisms of os¬motic adaptation. The mass spectrometry proteomics data is available at the ProteomeXchange Consortium via the PRIDE partner repository with the dataset identifier PXD037170.